Harnessing regulatory T cell neuroprotective activities for treatment of neurodegenerative disorders - Machhi, Jatin (Mol Neurodegener, 2020)
ABSTRACT: Emerging evidence demonstrates that adaptive immunity influences the pathobiology of neurodegenerative disorders. Misfolded aggregated self-proteins can break immune tolerance leading to the induction of autoreactive effector T cells (Teffs) with associated decreases in anti-inflammatory neuroprotective regulatory T cells (Tregs). An imbalance between Teffs and Tregs leads to microglial activation, inflammation and neuronal injury. The cascade of such a disordered immunity includes the drainage of the aggregated protein antigens into cervical lymph nodes serving to amplify effector immune responses. Both preclinical and clinical studies demonstrate transformation of this altered immunity for therapeutic gain. We posit that the signs and symptoms of common neurodegenerative disorders such as Alzheimer’s and Parkinson’s diseases, amyotrophic lateral sclerosis, and stroke can be attenuated by boosting Treg activities. GRAPHICAL ABSTRACT: [Image: see text]